Detection of high potential gold mineralization areas using Landsat 8 data in Northeastern Sudan [electronic resource] - Ahmed Salah Osman Ali, 1990-; Amin Beiranvand Pour, supervisor; Fakulti Geoinformasi Dan Harta Tanah (2014)
Thesis (Sarjana Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2014